2012
DOI: 10.1542/peds.2011-2118
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Maternal Depressive Symptoms on Growth of Preschool- and School-Aged Children

Abstract: Maternal depressive symptoms during infancy may affect physical growth in early childhood. Prevention, early detection, and treatment of maternal depressive symptoms during the first year postpartum may prevent childhood height-for-age ≤ 10th percentile among preschool- and school-aged children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 28 publications
1
40
0
1
Order By: Relevance
“…Findings from the present study suggest that omitted variable bias may underlie some of the mixed findings identified in the existing literature (19)(20)(21)(27)(28)(29) and demonstrate the importance of controlling for confounding factors when investigating the effects of maternal depressive symptoms on child health and development. Furthermore, findings highlight the importance of controlling for measures of maternal mental health when examining children's health outcomes.…”
Section: Discussionmentioning
confidence: 51%
“…Findings from the present study suggest that omitted variable bias may underlie some of the mixed findings identified in the existing literature (19)(20)(21)(27)(28)(29) and demonstrate the importance of controlling for confounding factors when investigating the effects of maternal depressive symptoms on child health and development. Furthermore, findings highlight the importance of controlling for measures of maternal mental health when examining children's health outcomes.…”
Section: Discussionmentioning
confidence: 51%
“…43,44 It is also a concern that the different sources of stress that children experience residing in violent households could lead to the intergenerational cycle of violence and food insecurity. 30 Further, young children who reside with depressed mothers are more likely to demonstrate externalizing and internalizing behavior problems, 20,45 as well as adverse impacts on executive functioning, 46 physical growth, 47 and health. 48 Thus, studying the longitudinal relationship between maternal health problems and food insecurity among households with young children may inform the development of broader social services to provide food and maternal health assistance that can improve children's futures in a variety of ways.…”
Section: Present Studymentioning
confidence: 99%
“…Postpartum depression affects the health of mothers, the growth (Nasreen et al, 2013;Surkan et al, 2012) and development of their children (Ali et al, 2013;Fihrer et al, 2009), and their partner's mood (Pinheiro et al, 2006). Postpartum depression is a major depressive disorder with an onset within 4 weeks after childbirth (American Psychiatric Association, 2013).…”
Section: Introductionmentioning
confidence: 99%